Protease inhibitor-associated bone mineral density loss is related to hypothyroidism and related bone turnover acceleration. Issue 5 (May 2017) - Kinai, Ei; Gatanaga, Hiroyuki; Mizushima, Daisuke; Nishijima, Takeshi; Aoki, Takahiro; Genka, Ikumi; Teruya, Katsuji; Tsukada, Kunihisa; Kikuchi, Yoshimi; Oka, Shinichi
Abstract: Background: Clinical and experiments evidence indicate that protease inhibitors (PI) can cause bone mineral density (BMD) loss. However, the mechanism of such loss remains obscure. Methods: This single-center, cross-sectional study included 184 HIV-infected patients treated with PI who underwent dual-energy X-ray absorptiometry scan. Serum phosphorus, percentage of tubular reabsorption of phosphate (%TRP), thyroid and parathyroid function (iPTH), vitamin D, osteocalcin (OC), urinary deoxypyridinoline (DPD), and urinary cross-linked N-telopeptide of type I collagen (u-NTx) were measured. Results: The rate of hypothyroidism in PI-users [32/117 (27%)] was double that in non-PI users [8/67 (12%), p  = 0.016] and was significantly associated with PI use in multivariate analysis [odds ratio (OR) 11.37, 95% confidence interval (CI) 1.358–95.17, p  = 0.025]. Spine BMD was significantly lower in hypothyroid patients than euthyroid, for both total population (−1.37 vs. −1.00, p = 0.041) and PI users (−1.56 vs. −1.13, p = 0.029). Multivariate regression analysis identified inverse correlation between hypothyroidism and spine BMD [estimate −0.437, 95% CI -0.858 to −0.024, p  = 0.042]. OC, DPD and u-NTx were significantly higher in PI users than in non-PI users ( p  = 0.01, 0.05, and 0.01, respectively). Conclusions: PI use is associated with hypothyroidism as well as bone turnover acceleration, which worsens PI-associated BMD loss. In PI-treated patients, thyroid function tests are warranted to prevent further progression of PI-associated BMD loss.